1992
DOI: 10.1007/bf00419755
|View full text |Cite
|
Sign up to set email alerts
|

Deletion analysis of the NH2-terminal region of ?-1,4-galactosyltransferase

Abstract: To determine the biological role, if any, of the NH2-terminal region of beta-1,4-galactosyltransferase (GT; EC 2.4.1.90), we constructed deletion mutants and expressed them in COS-7 cells. Each deletion construct was analyzed for enzymatic activity, protein production and mRNA transcription. All of the deletion mutants were transcribed to produce GT mRNA, but the GT protein was not detected in those constructs whose transmembrane (aa 14-42) domain was deleted. The results suggest that the transmembrane region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
5
30
0
Order By: Relevance
“…The mechanism by which this phase separation occurs may be similar to that in processes involved in protein sorting in biological systems, which were suggested to be mismatch-dependent (36)(37)(38)(39).…”
Section: Effects Of Peptides With Other Charged Flanking Residuesmentioning
confidence: 84%
“…The mechanism by which this phase separation occurs may be similar to that in processes involved in protein sorting in biological systems, which were suggested to be mismatch-dependent (36)(37)(38)(39).…”
Section: Effects Of Peptides With Other Charged Flanking Residuesmentioning
confidence: 84%
“…The transmembrane segment is native to the CD4 antigen, consisting of 26 aa, longer than typical ER or Golgi resident membrane proteins, which often have Ϸ15 aa. The longer transmembrane segment reduces the possible tendency toward ER or Golgi residence as affected by the heterogeneity of lipid thickness in the ER vs. the plasma membrane (11,12). The intracellular spacer that separates the transmembrane segment from the ER retention͞retrieval signals is the tandemly positioned peptide sequence of YPYDVPDYA corresponding to the HA epitope, a viral sequence that is hydrophilic and functions as a linear peptide (13).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis has suggested that transmembrane domains of ER͞Golgi residents are on average 5 amino acid residues shorter than those of plasma membrane residents (57). Experiments in unpolarized cells have shown that lengthening the transmembrane domain of Golgi resident proteins leads to their appearance on the plasma membrane (11)(12)(13). These data led to the suggestion that the sorting of membrane proteins in the exocytic pathway of eukaryotic cells is governed by hydrophobic matching of the transmembrane domains to increasingly thicker membranes along this pathway (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in unpolarized cells have shown that lengthening the transmembrane domain of Golgi resident proteins leads to their appearance on the plasma membrane (11)(12)(13). These data led to the suggestion that the sorting of membrane proteins in the exocytic pathway of eukaryotic cells is governed by hydrophobic matching of the transmembrane domains to increasingly thicker membranes along this pathway (11)(12)(13). Because in rat hepatocytes membrane proteins move from the ER to the Golgi to the basolateral plasma membrane before reaching the apical plasma membrane (58,59), an expectation would have been that bilayer thickness would have increased along this route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation